2018
DOI: 10.1016/j.compositesb.2018.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the effects of pure and salt water absorption on the rate-dependent response of an epoxy matrix

Abstract: The study reports the measured effects of water absorption on epoxy resin. Epoxy samples were exposed to wet conditioning environments including pure water, NaCl-water solution, and pure water at boiling temperature, measuring absorption as a function of time. Vickers hardness and indentation creep tests were performed and the mechanical response of the material to uniaxial stress was also measured in both compression and tension, at imposed strain rates in the range 0.001-2500 s -1 . It was found that the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Water exposure reduced the Young's modulus by 80%, and the strength by 50% on QS90 specimens, while reductions were of 80% and 58% (on E and σu, respectively) for QS45 specimens. QS90-WS and QS45-WS specimens (Figures 6,7) showed a higher strain to failure than fully dry specimens, in line with the slight increase in ductility of the matrix which we measured in [28].…”
Section: Effects Of Conditioning On the Mechanical Responsesupporting
confidence: 82%
See 3 more Smart Citations
“…Water exposure reduced the Young's modulus by 80%, and the strength by 50% on QS90 specimens, while reductions were of 80% and 58% (on E and σu, respectively) for QS45 specimens. QS90-WS and QS45-WS specimens (Figures 6,7) showed a higher strain to failure than fully dry specimens, in line with the slight increase in ductility of the matrix which we measured in [28].…”
Section: Effects Of Conditioning On the Mechanical Responsesupporting
confidence: 82%
“…Now focus on Figure 8b and Figure 8d: the strength of the QS90 specimens is, as expected, lower than the strength of the neat resin, due to the stress concentration induced by the presence of the fibres. While the measurements in [28] suggested that the strength of the matrix could be highly recoverable upon re-drying, for the composite this is not the case. This reinforces the notion that the fibre-matrix interface strength is permanently weakened by water absorption.…”
Section: Effects Of Conditioning On the Mechanical Responsementioning
confidence: 91%
See 2 more Smart Citations
“…In addition, the 10° specimens are noticeably lacking any significant nonlinear behaviour in the dynamic tests, Figure 4 d). Both of these differences can be attributed to the viscous stiffening and hardening of the matrix at higher strain-rates, which has been observed in [16].…”
Section: Resultsmentioning
confidence: 83%